Analisis Pengelolaan Pendapatan dan Belanja Daerah Pada Pemerintah Kota Banjarmasin - Husnul Abdi; Siti Rusidah; Hasanur Arifin (JURNAL BISNIS DAN PEMBANGUNAN, 2016)
This research is aimed at finding out to what extend the regional revenue and expenditure governance reaches the level of economic,efficiency  and affectivity values. Besides that, it also examines the policies conducted in order to use and optimize local revenues collection. Using descriptive method related to ” value for moner ” concepts, this research took place in Banjarmasin city and utilized primary dan secondary data of 2007,2008,2009,2010 and 2011. Primary data were collected from interviews with the Head Banjarmasin Municipal Revenue Agency Office and Head of budgeting departement,while secondary data were collected from budget realization report documents. The methode of economic,efficiency dan affectivity analysis was operated to measure the achievement in several relevant performance indicators. The economic  level of the governance during 2007-2011 reached 84,50 %, in average, while the efficiency level reached 95,24 % and the affectivity level reached 102,81 %.In optimizing local revenue collection,the ratio in valur for  money tool was useful in providing information to improve all regional goverment components performance,internally asa well as externally. Keywords : Value For Money,Revenue,Expenditure, economic,efficiency,affectivity